2020
DOI: 10.1088/1742-6596/1594/1/012020
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perspectives on the Design and Implementation of a Blended Learning in Practicum

Abstract: This research aimed to investigate the implementation of blended learning (BL), which was designed in a group of pre-service chemistry teachers at higher education institutions. Blended learning was implemented by holding face-to-face lectures combined with online lectures using the Schoology Learning Management System (LMS). Meanwhile, the research employed a qualitative approach. The purpose of this study was to discover learning experiences and perceptions of students who have applied BL in practical learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…On the contrary, in many other studies (Elkins, 2015; Yuliyanto et al, 2020), students' satisfaction was found to be statistically significant toward hybrid classes more than face‐to‐face or online only. For example, in the study conducted by Yuliyanto et al (2020), hybrid learning was executed by holding face‐to‐face sessions combined with online lectures using the LMS.…”
Section: Literature Reviewmentioning
confidence: 66%
See 2 more Smart Citations
“…On the contrary, in many other studies (Elkins, 2015; Yuliyanto et al, 2020), students' satisfaction was found to be statistically significant toward hybrid classes more than face‐to‐face or online only. For example, in the study conducted by Yuliyanto et al (2020), hybrid learning was executed by holding face‐to‐face sessions combined with online lectures using the LMS.…”
Section: Literature Reviewmentioning
confidence: 66%
“…On the contrary, in many other studies (Elkins, 2015; Yuliyanto et al, 2020), students' satisfaction was found to be statistically significant toward hybrid classes more than face‐to‐face or online only. For example, in the study conducted by Yuliyanto et al (2020), hybrid learning was executed by holding face‐to‐face sessions combined with online lectures using the LMS. Their results revealed that students found new experiences with the hybrid approach resulted in feeling more independent, flexible, and at ease in working on learning difficulties.…”
Section: Literature Reviewmentioning
confidence: 66%
See 1 more Smart Citation
“…"Online provides broad opportunities for students to learn independently, especially those who have high learning creativity, and F2F is to facilitate and motivate slow students" (Mirabella* et al, 2004;Wilke et al, 2016;Zwart et al, 2017;Kissau, 2015;Tambunan et al, 2020). (Singh et al, 2021a, b) • The frequent number of meetings during a week would support a better quality of learning (Graham et al, 2013;Yuliyanto et al, 2020) Assessments (A)…”
Section: Building Blocks For Future Blended Learningmentioning
confidence: 99%
“…• Ensuring the availability of technical support during exams to avoid any anxiety caused by those technical issues (Yuliyanto et al, 2020) • Conduction of F2F assessments on LMS (Prasetyo et al, 2022) Health care (HC)…”
Section: Pedagogical (P)mentioning
confidence: 99%